Additive Effects of PS1 and APP Mutations on Secretion of the 42-Residue Amyloid β-Protein - Martin Citron; Christopher B. Eckman; Thekla S. Diehl; Chris Corcoran; Beth L. Ostaszewski; Weiming Xia; Georges Levesque; Peter St. George Hyslop; Steven G. Younkin; Dennis J. Selkoe (Neurobiology of Disease, 1998)
Humans harboring missense mutations in the presenilin 1 (PS1) gene undergo progressive cerebral deposition of the 42-residue amyloid β-protein (Aβ42) at an early age and develop severe Alzheimer's disease. Aβ42is selectively elevated in the conditioned media of cells expressing mutant but not wild-type PS1, indicating that presenilin mutations alter APP processing. Here we analyze the effects of various PS1 mutant constructs on the cellular production of Aβ42. A construct expressing only the PS1 N-terminal endoproteolytic fragment with the mutation Y115H causes no significant increase in Aβ42, whereas a full-length PS1 construct with the same mutation does. This result suggests that the pathogenic effect of mutant presenilins is produced by the full-length molecule even though only a minor proportion of total PS1 occurs as holoprotein in tissues and cell lines. We demonstrate that the effects of two different PS1 mutations are additive when engineered into the same PS1 molecule. Therefore, two mutations alter γ-secretase processing of APP more than one and the PS1 mutations described to date do not cause the maximum possible PS1-mediated rise in Aβ42. When a PS1 mutation was expressed in cells carrying the APPV717Imutation, Aβ42rose dramatically to become the predominant secreted Aβ species, an observation of interest for transgenic modeling of AD. Our results are consistent with the hypothesis that presenilin is a major regulator of the proteolytic processing of APP by γ-secretases.